2005
DOI: 10.1521/suli.35.1.14.59266
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Roles of Anxiety, Depression, and Hopelessness on Adolescent Suicidal Behaviors

Abstract: The purpose of this study was to explore the roles of anxiety, depression, and hopelessness as mediators between known risk factors and suicidal behaviors among 1,287 potential high school dropouts. As a step toward theory development, a model was tested that posited the relationships among these variables and their effects on suicidal behaviors. Structural equation models, estimated separately by gender, revealed support for the model, and substantial similarities between males and females. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
75
1
12

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(103 citation statements)
references
References 63 publications
15
75
1
12
Order By: Relevance
“…This is consistent with 16 previous findings that adolescents who had inadequate problem-solving skills were at increased risk for suicidal thoughts and behaviors (e.g., Kingsbury et al, 1999;Thompson, et al, 2005). Moreover, results showed that a higher level of hopelessness was associated with a higher level of adolescent suicidal ideation.…”
Section: Discussion 15supporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with 16 previous findings that adolescents who had inadequate problem-solving skills were at increased risk for suicidal thoughts and behaviors (e.g., Kingsbury et al, 1999;Thompson, et al, 2005). Moreover, results showed that a higher level of hopelessness was associated with a higher level of adolescent suicidal ideation.…”
Section: Discussion 15supporting
confidence: 92%
“…Although previous studies had found that hopelessness mediated the relationship between other personal factors (e.g., depression, anxiety, and rumination) and suicidal ideation (e.g., MacLeod et al, 2005;Smith et al, 2006;Thompson, et al, 2005), this study was pioneering in identifying the mediating role of hopelessness between 20 emotion competence, parent-adolescent communication, family functioning, and adolescent suicidal ideation, which was different from Levy et al's (1995) findings.…”
Section: Discussion 15contrasting
confidence: 83%
See 1 more Smart Citation
“…This implies that traditional Asian communication norms reduce the openness and expressiveness used in communication. Family emotional expressiveness as an indicator of family support was related to suicidal behaviors in adolescents and the absence of family expressiveness may contribute to an elevated risk for the onset of suicidal behaviors (20). Conversely, family cohesion may be a protective factor against suicidal behaviors (5).…”
Section: Discussionmentioning
confidence: 95%
“…Ebenso wie beim pathologischen Internetkonsum stehen auch diese Verhaltensweisen in deutlichem Zusammenhang mit psychischen Problemen und insbesondere Depressivität (Brunner et al, 2007;Thompson, Mazza, Herting, Randell, Eggert, 2005). Epidemiologische Untersuchungen eines Zusammenhangs von pathologischer Internetnutzung mit selbstverletzenden sowie suizidalen Verhaltensweisen im Jugendalter gibt es bisher in Deutschland nicht.…”
Section: Hintergrundunclassified